Environmental factors in benign migratory glossitis and psoriasis: Retrospective study of the association of emotional stress and alcohol and tobacco consumption with benign migratory glossitis and cutaneous psoriasis. (30th July 2014) - Gonzaga, H.F.S.; Chaves, M.D.; Gonzaga, L.H.S.; Picciani, B.L.S.; Jorge, M.A.; Dias, E.P.; Tomimori, J.
Abstract Background The association between benign migratory glossitis (BMG) and psoriasis (PS) has been reported in the literature. Objective This study aimed to determinate the environmental factors related to BMG and PS and to investigate their interactions. Methods The study population included 129 patients with PS, 399 patients with BMG and a control group (CG) of 5472 individuals with neither PS nor BMG. The environmental factors evaluated in this study included alcohol and tobacco consumption and emotional stress. The Pearson's chi‐squared test was used for analysing the association of the environmental factors with PS and BMG. Results The prevalence of alcohol consumption in the PS group was significantly higher than that in the CG. Tobacco consumption had a weak negative association with the BMG group. With respect to the PS group, no statistically significant association was observed. Emotional stress was the most important factor in the two study groups. Emotional stress and alcohol use together presented a higher incidence in the study groups than in the CG. Emotional stress and tobacco consumption together had a three times higher incidence in the PS group than in the BMG group. The association of emotional stress, alcohol and tobacco consumption in the PS group was four times higher than that in the CG. Limitations This study was limited by the lack of the information about frequency, type and length time of use of tobacco and alcohol, and by difficult to measure stress thought self‐report questionnaire. Conclusion The interactions between PS and environmental factors differ from those between BMG and environmental factors. These differences among interactions may be responsible for different forms of manifestations of these diseases, considering being both the same disease.